Sophocles Antigone and other tragedies - Sophocles ca. 497/496 v. Chr.-406 v. Chr (Oxford University Press, 2020)
"Sophocles stands as one of the greatest dramatists of all time, and one of the most influential on artists and thinkers over the centuries. His plays are deeply disturbing and unpredictable, unrelenting and open-ended, refusing to present firm answers to the questions of human existence, or to provide a redemptive justification of the ways of gods to men-or women. These three tragedies portray the extremes of human suffering and emotion, turning the heroic myths into supreme works of poetry and dramatic action. Antigone's obsession with the dead, Creon's crushing inflexibility, Deianeira's jealous desperation, the injustice of the gods witnessed by Hyllus, Electra's obsessive vindictiveness, the threatening of insoluble dynastic contamination ... Such are the pains and distortions and instabilities of Sophoclean tragedy. And yet they do not deteriorate into cacophony or disgust or incoherence or silence: they face the music, and through that the suffering is itself turned into the coherence of music and poetry. These original and distinctive verse translations convey the vitality of Sophocles' poetry and the vigour of the plays in performance, doing justice to both the sound of the poetry and the theatricality of the tragedies. Each play is accompanied by an introduction and substantial notes on topographical and mythical references and interpretation. Antigone is an icon of Greek tragedy, and Antigone is herself a tragic icon in world theatre. Sophocles' best-known and most performed play tells a story of defiance and the impossible demands of loyalty. Deianeira, also known as Women of Trachis or Trachinaian Women, wrestles with the anxieties of matrimony and motherhood, following the doomed attempt by the wife of the hero Heracles to assert her dignity. Electra portrays a vengeful daughter's journey through unflagging grief and murderous fury, ending without resolution in uncertainty and suspense"--